(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
This study presents a comprehensive and systematic analysis of the Global Innovation Index (GII) data for selected countries in the South Caucasus and Latin America over the period 2013–2023. A broad set of countries was included to allow for data normalization and ensure comparability of results across different innovation systems. The research examines the strengths and weaknesses of national innovation ecosystems and addresses the challenges of uniform cross-country comparisons by employing the GII as a standardized and internationally recognized framework. Drawing on advanced statistical techniques adapted from the European Commission’s European Innovation Scoreboard methodology, the study evaluates the performance of the selected countries, classifies them into innovation categories, and provides rigorous evidence-based insights for policy development. A distinctive contribution of this research lies in its comparative focus on two geographically and economically diverse regions, thereby generating novel and actionable policy implications for innovation-driven growth. The analysis further disaggregates the main components of the GII to reveal both their enabling factors and inherent limitations, and formulates context-specific recommendations. The study concludes by ranking the selected countries, offering valuable input for national and regional innovation policy design. To the best of the authors’ knowledge, this is the first study to systematically and explicitly compare the innovation performance of South Caucasus economies with that of Latin American countries.